A review of candonid ostracods (Crustacea: Ostracoda: Podocopida) from East sia, with descriptions of five new species from South Korea - Karanovic, Ivana; Lee, Wonchoel (Zootaxa, 2012)
Seven species of the family Candonidae Kaufmann, 1900 are reported from South Korea. Five species are described as new, all belonging to the subfamily Candoninae Kaufmann, 1900 and the tribe Candonini Kaufmann, 1900: Candona quasiakaina sp. nov., C. sillae sp. nov., Fabaeformiscandona koreana sp. nov., Typhlocypris choi sp. nov., and Schellencandona tea sp. nov. A very close resemblance between Candona sillae and the European C. improvisa Ostermeyer, 1937 prompted a redescription of the latter species based on the type material, and designation of the lectotype. One species of the tribe Candonopsini, Candonopsis transgrediens Brehm, 1923, previously known only from China, is reported from Korean freshwater habitats, and its first redescription is provided, along with a key to the world representatives of the genus Candonopsis Vávra, 1820. One species of the subfamily Paracypridinae, Dolerocypria mukaishimensis Okubo, 1980, previously known only from Japan, is redescribed from Korean brackish water habitats, and some notes on its variability are provided. A checklist of the Candonidae ostracods from East Asia is also provided, but only for those species that have been well-documented and taxonomically described.